The educommunication in environmental education pratics: Experience’s report of the Selective Collection Extension Project – CEUNES/UFES - Lima Correia, Francielli; Simões Fassarella, Simone (Guará Journal, 2015)
This qualitative research aims to foment the communication and social-environmental education reflection through workshops developed by a Selective Collection Extension Project. It is understood thatenvironmental education needs to be guided by the promotion of an active citizenship considering their sense of belonging and accountability that, in organized civil society, aims to overcome the social risks generators and their social-environmental conflicts. In this context, the Environmental Educommunication presents itself as a people’s active involvement in the environmental improvement critical awareness political-pedagogic strategy. This paper presents the educommunication based social-environmental workshops experience’s report carried out by the Selective Collection Extension Project. The workshops enabled the participants’ awareness regarding the social generators of social-environmental risks and the need for promoting local actions aimed at building a sustainable society
Keywords: Educommunication; Environmental education; University extension projetcs